Evaluating the Effect of the Demographic, Trichoscopic and Laboratory Characteristics on The Recurrence of Alopecia Areata - Didem Kazan (Mattioli1885, 2024)
Introduction: Alopecia areata (AA) has diverse disease characteristics and multiple factors may interfere with the prognosis of the disease. Objectives: In this study, the factors affecting the AA recurrence were evaluated. Methods: A total of a hundred patients diagnosed with AA between June 2022 and March 2023 were included in this retrospective, cross-sectional study. The patients were divided into two groups according to the presence of outbreaks. Both groups were compared in terms of age, gender, disease duration, number of outbreaks, family history of AA, previous medical treatment history for AA, clinical type, disease severity, presence of accompanying nail findings, and trichoscopic and laboratory characteristics. Results: Among 100 patients, male dominance was found (N = 69). Most of the patients had patchy disease (90/100), mild disease severity (88/100), and a solitary outbreak (65/100). Male gender, longer disease duration, family history, presence of S2 severity of alopecia tool score, trachyonychia, short vellus hairs in trichoscopic examination, hypothyroidism, and folic acid deficiency were factors for AA outbreaks. Male gender and the presence of a family member with AA in the family were defined as the independent prognostic factors for disease recurrence. Conclusions: While demographic, laboratory, and clinical findings are factors for AA outbreaks in the follow-up, male gender and family history should be considered independent predictors.